Kesiapan Remaja Putri Menuju Menarche - Haslan, Hasliana; Nur Eva Sapartina; Andi Ramliyani Hasyim (Akademi Kebidanan Tahirah Al Baeti Bulukumba, 2025)
In the life cycle, puberty is an important stage in the development of sexuality. In women, puberty generally begins at the age of 10-15 years and lasts for approximately 4 years. Puberty is marked by rapid body growth, first menstruation (menarche), psychological changes and the emergence of secondary sexual characteristics. When facing menarche, good mental readiness is needed. Readiness to face the first menstruation is a condition that indicates that a person is ready to achieve one of the physical maturations, namely the arrival of the first menstruation (menarche), which comes from a special place for women when they reach the age of ten to sixteen years. The purpose of this service is to increase the knowledge of adolescent girls about preparing for menarche and reduce the anxiety of adolescents when facing menarche. Participants in this activity were students (adolescent girls) who were in grades V and VI in the 2024/2025 academic year, namely 18 students. The stages of the activity consist of preparation, implementation and evaluation. The implementation of the activity began with a pre-test, implementation of Adolescent Reproductive Health education and ended with a post-test to measure the level of student understanding. The activity went smoothly and all targets were present in the activity. The results of the activity were obtained as many as 72% of students experienced an increase in knowledge after participating in the education.